Evaluation of both overall and individual FMS components results in male and female groups: a systematic review and meta-analysis - Ahmad, Muhammad Ibrar; Zhang, Yi; Younas, Muhammad Talha; Parveen, Ayesha; Shi, Yu; Lu, Yunhang; Song, Zhengxue (Frontiers in Physiology, 2026)
ObjectivesThis meta-analysis aimed to identify gender-based differences of both overall Functional Movement Screen (FMS) and individual FMS components in male and female groups.MethodsA comprehensive search was performed across three major databases (PubMed, Web of Science, and Google Scholar) to ensure rigorous inclusion criteria. Data collection took place from 2016 to 2024, and 1,235 articles were identified. After scrutiny, 20 met the requirements for inclusion. The Review Manager 5.4 and CMAv4 software were utilized to examine the FMS score results to ensure rigorous statistical evaluation. Data were synthesized using a random-effect model, with the Mean difference (MD) and 95% confidence interval (CI) used to calculate effect size.ResultsThe overall FMS score showed that the functional movement capacities of males and females differed; females performed higher (MD = −0.46, 95% CI = −0.83 to −0.08, P = 0.02) compared to males. A meta-analysis of 7 individual FMS components was conducted to assess the importance for both sexes. However, tests on specific areas showed significant gender differences: females outperformed males in shoulder mobility (p < 0.00001), active straight leg raise (p < 0.00001), hurdle step (p = 0.01), and rotary stability (p = 0.002). In contrast, males demonstrated significantly greater trunk stability (p < 0.0001) compared to females. Despite this, the in-line lunge (p = 0.42) and deep squat (p = 0.20) demonstrated no significant difference across gender.ConclusionThese outcomes highlight significant gender-based differences that can help identify weaknesses and strengths, which may assist coaches, trainers, and individuals in recommending gender-specific exercises and training programs.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=1043946, identifier CRD420251043946.